Legal Protection Costumer About Manipulation Fake Import Beauty Cream - Agung Hari Laksono; Soemali (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
Cosmetics are one of the necessities of human life, especially women in fulfilling the demands of their beauty. There have been many cases of counterfeit and / or illegal cosmetics circulating in the cosmetics distribution. Rahajeng Ratnasari alias Sari is a business actor who sells fake cosmetics with his own concoctions in the city of Mojokerto. The objectives of this study are: 1) to identify and analyze the actions of the business actor as an act against the law. 2) to find out and analyze the form of legal protection for consumers due to illegal acts committed by the business actor. This type of research is Normative using the Statute Approach method. This study also uses the Conceptual Approach method. The result of this research is that the actions of business actors in marketing their products can be categorized as acts against the law and Law Number 8 of 1999 concerning Consumer Protection. The form of legal protection for consumers due to illegal acts committed by business actors is the formation of a consumer protection agency as a consumer that builds protection and provides space in consumer dispute disputes through the Consumer Dispute Resolution Agency as a small lawsuit court body.